Influence of Psychological Stress and Moderate Physical Activity in Cardiovascular Reactivity - Milagros Lisset León Regal; Yandy García Álvarez; Rosmari Álvarez Hernández; Cynthia Morales Pérez; Víctor Manuel Regal Cuesta; Hermes David González León (Revista Finlay)
Reactivity is the response of the homonymous system to an external stimulus and it is modified by various parameters among them the psychological one which influences the appearance of cardiovascular diseases. Some studies have demonstrated and supported the benefits of physical activity in keeping ideal physiological and psychological fitness, including cardiovascular response to acute stress. This work had the objective of describing the influence of psychological stress and aerobic physical activity on cardiovascular reactivity. For that a total of 30 bibliographic sources, among them 2 books and a number of articles from scientific journals, accessed through the main managers the computer network. It was concluded that psychological stress and aerobic physical exercises influence antagonistically on cardiovascular reactivity.